2021
DOI: 10.1038/s41423-021-00749-x
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of CAR-T cells with PD-1 and TCR disruption in mesothelin-positive solid tumors

Abstract: Programmed cell death protein-1 (PD-1)-mediated immunosuppression has been proposed to contribute to the limited clinical efficacy of chimeric antigen receptor T (CAR-T) cells in solid tumors. We generated PD-1 and T cell receptor (TCR) deficient mesothelin-specific CAR-T (MPTK-CAR-T) cells using CRISPR-Cas9 technology and evaluated them in a dose-escalation study. A total of 15 patients received one or more infusions of MPTK-CAR-T cells without prior lymphodepletion. No dose-limiting toxicity or unexpected ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(105 citation statements)
references
References 36 publications
2
102
0
1
Order By: Relevance
“… 80 , 81 , 82 Phase I clinical trials demonstrated that CRISPR-Cas9 guided disruption of PDCD1 does not lead to uncontrolled CAR T cell proliferation or persistence. 83 While the impact of PDCD1 knockout on CAR T immunotherapeutic clinical efficacy is still under investigation, these discoveries suggest that extrinsic and intrinsic blockade of the PD-1/PD-L1 axis protect CAR T cells from PD-1 induced exhaustion ( Figure 2 a).
Figure 2 Intrinsic T cell approaches to overcoming exhaustion in CAR T cell therapy.
…”
Section: Targeting T Cell Intrinsic Pathways To Overcome Exhaustion I...mentioning
confidence: 99%
“… 80 , 81 , 82 Phase I clinical trials demonstrated that CRISPR-Cas9 guided disruption of PDCD1 does not lead to uncontrolled CAR T cell proliferation or persistence. 83 While the impact of PDCD1 knockout on CAR T immunotherapeutic clinical efficacy is still under investigation, these discoveries suggest that extrinsic and intrinsic blockade of the PD-1/PD-L1 axis protect CAR T cells from PD-1 induced exhaustion ( Figure 2 a).
Figure 2 Intrinsic T cell approaches to overcoming exhaustion in CAR T cell therapy.
…”
Section: Targeting T Cell Intrinsic Pathways To Overcome Exhaustion I...mentioning
confidence: 99%
“…The use of CRISPR/Cas9 gene editing technology opens a new world for the upgrading of fourth-generation CAR T cells ( Figure 4 ). Recently, several clinical trials by Stadtmauer ( 128 ), Lu ( 129 ), Wang ( 130 ), and Simon ( 131 ) confirmed the clinical feasibility and safety of CRISPR/Cas9- modified T cells.…”
Section: Clinical Application Of Crispr Cas9-related Pd-1/pd-l1mentioning
confidence: 96%
“…The most widely studied inhibitory receptor is PD-1. Knocking out PD-1 in CD8 + T cells with the CRISPR/Cas9 system was demonstrated to have antitumor effects in several preclinical and clinical studies, including studies on cancers including melanoma, glioblastoma, ovarian cancer, prostate cancer, B-cell lymphoma, gastric cancer, and breast cancer [ 181 – 189 ]. In addition, gene editing can be used to reverse inhibitory signaling.…”
Section: Cell Reprogrammingmentioning
confidence: 99%
“…Fusing PD-1 expressed by CD8 + T cells to CD28 via CRISPR/Cas9 gene editing reverses the original inhibitory signaling to achieve stimulatory cell signaling. This reprogramming strategy ultimately restores the effector function of exhausted CD8 + T cells [ 187 189 ].…”
Section: Cell Reprogrammingmentioning
confidence: 99%